2012
DOI: 10.1371/journal.pone.0052050
|View full text |Cite
|
Sign up to set email alerts
|

Monophyly or Paraphyly– The Taxonomy of Holcoglossum (Aeridinae: Orchidaceae)

Abstract: Recently, there have been a lot of intense debates about the acceptance/rejection of paraphyletic groups in biological classification. On the one hand, evolutionary classification states that similarity and common descent are two criteria for biological classification and paraphyletic groups are natural units of biological classification. On the other hand, cladistic classification considers that common descent is the only criterion in biological classification and monophyly should be strictly adhered to. Holc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Recent 62 phylogenetic analyses that relied on nucleotide sequences have 63 addressed relationships in the group. With the exception of several 64 studies focusing on some individual groups, such as the Vanda alliance (e.g., Kocyan et al, 2008;Gardiner et al, 2013;66 Xiang et al, 2012;Zhang et al, 2013) and Phalaenopsis (e.g., 67 Padolina et al, 2006;Tsai et al, 2010;Yukawa et al, 2005), the phy-68 logeny of Aeridinae was reconstructed by Topik et al (2005) and 69 Topik et al (2012) based on the analyses of two DNA regions (ITS 70 and matK) in 75 taxa belonging to 62 genera and 82 taxa belonging 71 to 66 genera, respectively. Both studies suggested that the mono-72 phyly of Aeridinae was tentatively supported.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent 62 phylogenetic analyses that relied on nucleotide sequences have 63 addressed relationships in the group. With the exception of several 64 studies focusing on some individual groups, such as the Vanda alliance (e.g., Kocyan et al, 2008;Gardiner et al, 2013;66 Xiang et al, 2012;Zhang et al, 2013) and Phalaenopsis (e.g., 67 Padolina et al, 2006;Tsai et al, 2010;Yukawa et al, 2005), the phy-68 logeny of Aeridinae was reconstructed by Topik et al (2005) and 69 Topik et al (2012) based on the analyses of two DNA regions (ITS 70 and matK) in 75 taxa belonging to 62 genera and 82 taxa belonging 71 to 66 genera, respectively. Both studies suggested that the mono-72 phyly of Aeridinae was tentatively supported.…”
mentioning
confidence: 99%
“…Wood (1990) lyses may lead to incorrect topologies (Meimberg et al, 2006). Of all of the taxa in Aeridinae, this group has recently received 327 the most attention (Christenson, 1987;Gardiner, 2012;Gardiner 328 et al, 2013;Liu et al, 2011;Xiang et al, 2012;Zhang et al, Seidenfaden, 1992). In fact, the greatest difference between the 393 two genera is that Trichoglottis has short inflorescences and the lat-394 ter has long inflorescences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of Holcoglossum and Papilionanthe have whitish flowers and relatively long spurs (ca. 1-1.5 cm; Topik et al, 2005;Kocyan et al, 2008;Xiang et al, 2012), which may be pre-adaptations to pollination by moths.…”
Section: Resultsmentioning
confidence: 99%
“…Christenson [10] divided Holcoglossum into two sections based on the flower number per inflorescence and plant form. Jin [12] proposed an infrageneric system based on floral characteristics, such as the callus, spur and stipe; this system has been supported by the results of recent molecular phylogenetic studies [13], [20]. However, four species in Jin's system, H. omeiense X. H. Jin & S. C. Chen, H. lingulatum (Averyanov) Averyanov, H. wangii Christenson and H. kimballianum (Rchb.…”
Section: Introductionmentioning
confidence: 91%